Dari Ecoliteracy Menuju Ecoaction: Pemberdayaan Masyarakat Melalui Inovasi Produk Ramah Lingkungan untuk Keberlangsungan Bumi - Nukhbatul Bidayati Haka; Hardiyansyah Masya; Mivtha Citrainingrum (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2025)
Environmental degradation driven by low community awareness and limited sustainable practices poses a critical challenge for local development. This community engagement program aims to bridge the gap between environmental knowledge (eco-literacy) and practical action (eco-action) by empowering residents to innovate environmentally friendly products. Specifically, the program integrates eco-literacy training with hands-on technical skills in ecoprint production and the conversion of used cooking oil into eco-friendly candles. The activities, conducted in Paya Village, Pesawaran Regency, involved 60 participants, including fifth-grade elementary students, housewives, and village youth groups. A participatory action approach was implemented through three main stages: (1) socialization to enhance eco-literacy, (2) direct training on eco-product innovation, and (3) mentoring and evaluation of product quality and sustainability impact. The outcomes demonstrate a significant improvement in participants’ eco-literacy and technical competence in creating value-added eco-products, utilizing leaf and flower waste for ecoprint designs and used cooking oil for aromatic candles. Beyond waste reduction, the initiative fostered alternative income opportunities and reinforced intergenerational collaboration between youth and adults. The novelty of this program lies in its dual integration of eco-literacy education and product innovation through intergenerational learning, advancing previous community service models that typically focused on either environmental education or product-based empowerment. This approach highlights the transformative potential of linking environmental awareness with entrepreneurial sustainability and recommends replication in other community-based economic–ecological resilience programs.